1996
DOI: 10.2105/ajph.86.10.1422
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in children with severe mental retardation: the effect of placement.

Abstract: OBJECTIVES: This study was undertaken to assess the predictors of mortality in severely disabled children with mental retardation, and to compare risk-adjusted mortality rates for those living in institutions with rates for those living in the community. METHODS: Statistical analysis was performed on a set of 24,469 person-years, derived from a population of all children with severe mental retardation and a fragile medical condition who are registered with the California Department of Developmental Services. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Other studies focused on comparable mortality rates between community settings and institutions (Eyman, Grossman, Tarjan, & Miller, 1987). Some studies in California have indicated that community settings have higher mortality rates than institutions (Strauss, Eyman, & Grossman, 1996;Strauss & Kastner, 1996;Strauss et al, 1998aStrauss et al, , 1998b. On the other hand, Silverman, Zigman, and Silver (1992) found that movement of adults with profound intellectual disability and multiple disabilities from a service-intensive, skilled nursing facility (SNF) to small, community-based ICF/MRs did not increase mortality risk.…”
Section: Residential Characteristicsmentioning
confidence: 99%
“…Other studies focused on comparable mortality rates between community settings and institutions (Eyman, Grossman, Tarjan, & Miller, 1987). Some studies in California have indicated that community settings have higher mortality rates than institutions (Strauss, Eyman, & Grossman, 1996;Strauss & Kastner, 1996;Strauss et al, 1998aStrauss et al, , 1998b. On the other hand, Silverman, Zigman, and Silver (1992) found that movement of adults with profound intellectual disability and multiple disabilities from a service-intensive, skilled nursing facility (SNF) to small, community-based ICF/MRs did not increase mortality risk.…”
Section: Residential Characteristicsmentioning
confidence: 99%
“…The importance of quality of life has been tied to outcomes following de-institutionalization. Strauss et al [1996] found that persons with IDD were at increased risk of death in community settings compared with institutions when level of…”
Section: Quality Of Lifementioning
confidence: 99%
“…[49][50][51][52] suggested that initially one should partition the children into cohorts on the basis of two key variables. These were tube feeding (a dichotomy according to whether the child required gastrostomy feeding), and a four-point mobility scale (cannot lift head when lying on stomach/can lift head but not chest/can lift head and chest when lying on stomach but has limited ability to roll/has full rolling ability).…”
Section: Application 1: Prognostic Chartsmentioning
confidence: 99%